2023
DOI: 10.3847/psj/acaf78
|View full text |Cite
|
Sign up to set email alerts
|

The Enigmatic Abundance of Atomic Hydrogen in Saturn’s Upper Atmosphere

Abstract: A planet’s Lyα emission is sensitive to its thermospheric structure. Here we report joint Hubble Space Telescope and Cassini cross-calibration observations of the Saturn Lyα emission made 2 weeks before the Cassini grand finale. To investigate the long-term Saturn Lyα airglow observed by different ultraviolet instruments, we cross-correlate their calibration, finding that while the official Cassini/UVIS sensitivity should be lowered by ∼75%, the Voyager 1/UVS sensitivities should be enhanced by ∼20% at the Lyα… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 53 publications
4
7
0
Order By: Relevance
“…The revised Voyager Lyα brightnesses are roughly consistent with those observed by Cassini/UVIS (Koskinen et al 2020). Using HST observations from an Earth orbit as a calibration standard, Ben-Jaffel et al (2023) challenged the downward revision of the Voyager brightnesses and proposed instead a recalibration of the Cassini/ UVIS instrument at Lyα that would increase the observed brightnesses by 80%. After scaling with the solar Lyα flux at different times, they compared several observations by Cassini/ UVIS (in 2007, 2013, and 2014), HST/STIS (in 2017), and HST's Goddard High Resolution Spectrograph (in 1996) to arrive at this conclusion.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…The revised Voyager Lyα brightnesses are roughly consistent with those observed by Cassini/UVIS (Koskinen et al 2020). Using HST observations from an Earth orbit as a calibration standard, Ben-Jaffel et al (2023) challenged the downward revision of the Voyager brightnesses and proposed instead a recalibration of the Cassini/ UVIS instrument at Lyα that would increase the observed brightnesses by 80%. After scaling with the solar Lyα flux at different times, they compared several observations by Cassini/ UVIS (in 2007, 2013, and 2014), HST/STIS (in 2017), and HST's Goddard High Resolution Spectrograph (in 1996) to arrive at this conclusion.…”
Section: Introductionsupporting
confidence: 54%
“…In addition to scattered solar flux, a galactic contribution to the background of 40 R has been identified at large heliocentric distances (Gladstone et al 2021;Pryor et al 2022). While there remains uncertainty on the density of the LISM, we compare Cassini/UVIS Lyα observations to the model of Quémerais et al (2013a) and find good agreement between Cassini/UVIS observed and modeled brightnesses, without the proposed recalibration by a factor of 1.7 (Ben-Jaffel et al 2023;Pryor et al 2024). Limb observations and solar occultations, in conjunction with photochemical models, can provide further constraints on the atomic hydrogen columns, Lyα emissions.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…There are still differing opinions on the interstellar hydrogen density; for example, models presented in Katushkina et al (2017) used an interstellar value of 0.14 cm −3 , as did Model 3 of Izmodenov & Alexashov (2015), lower than the estimate of 0.21 cm −3 just found here. Now that we have an estimate for the decline in Cassini UVIS sensitivity at Lyα, it will be interesting to see how this affects studies of the Saturn Lyα dayglow from UVIS observations (e.g., Ben-Jaffel et al 2023).…”
Section: Discussionmentioning
confidence: 99%